2024
DOI: 10.1002/brb3.3456
|View full text |Cite
|
Sign up to set email alerts
|

Predictive model for identifying mild cognitive impairment in patients with type 2 diabetes mellitus: A CHAID decision tree analysis

Rehanguli Maimaitituerxun,
Wenhang Chen,
Jingsha Xiang
et al.

Abstract: BackgroundAs the population ages, mild cognitive impairment (MCI) and type 2 diabetes mellitus (T2DM) become common conditions that often coexist. Evidence has shown that MCI could lead to reduced treatment compliance, medication management, and self‐care ability in T2DM patients. Therefore, early identification of those with increased risk of MCI is crucial from a preventive perspective. Given the growing utilization of decision trees in prediction of health‐related outcomes, this study aimed to identify MCI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…In this study, we found patients with more diabetic complication, particularly diabetic nephropathy, will more likely to develop incident MCI during follow-up. Both diabetic nephropathy and cognitive impairment share common risk factors such as poor glycemic control, hypertension, lymphatic dysfunction and dyslipidemia ( 24 , 25 ). Therefore, the results of this study implied the importance of strengthening the management of diabetic complications to prevent or delay the onset of cognitive impairment in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found patients with more diabetic complication, particularly diabetic nephropathy, will more likely to develop incident MCI during follow-up. Both diabetic nephropathy and cognitive impairment share common risk factors such as poor glycemic control, hypertension, lymphatic dysfunction and dyslipidemia ( 24 , 25 ). Therefore, the results of this study implied the importance of strengthening the management of diabetic complications to prevent or delay the onset of cognitive impairment in clinical practice.…”
Section: Discussionmentioning
confidence: 99%